Headache In Children - Srinivasa R (Annals of Indian Academy of Neurology, 2002)
Headaches are common in children. The presentation of headache in children is varied and hence the characterization of headache is more challenging. This situation is worsened further by inadequacies in the history and the effect of maturational factors. Relevant epidemiological and limitations in the applicability of International Headache Society criteria in childhood headache and the rationale for newer criteria are discussed. Migraine and tension-type headache are the common primary headache seen in children. Although there is a paucity of clinical trials the management of childhood migraine, the important role of correct pharmacological approach has been delineated. The pivotal role of non-pharmacological treatment is emphasized.